Development and Validation of Stability Indicating UV-Spectrophotometric Method for the Simultaneous Estimation of Telmisartan and Metformin Hydrochloride in Bulk Drugs - Development, Development; Telmisartan, Validation of Stability Indicating UV-Spectrophotometric Method for the Simultaneous Estimation of; Drugs, Metformin Hydrochloride in Bulk (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: In present work attempt has been made to develop and validate a simple and sensitive UV spectrophotometric method for simultaneous estimation of Telmisartan and Metformin Hydrochloride. Objectives: To develop simple, precise, robust, sensitive and accurate UV-Spectrophotometric method for the simultaneous estimation of Telmisartan and Metformin HCl and to formulate the combined tablet dosage formulation of Telmisartan and Metformin HCl respectively. Methods: The optimum condition for the analysis of the drug was established with Methanol as solvent. Maximum absorption wavelength were found to be 296nm and 237nm for Telmisartan and Metformin Hydrochloride. It showed linear response between the concentration ranges of 2-12μg/ml and 0.1-0.6 μg/ml for Telmisartan and Metformin Hydrochloide espectively. The linear regression coefficient was found to be 0.999. The method was validated for linearity, Precision, ruggedness, specificity, Sensitivity as per ICH guidelines and all the values of validation was found to be within the acceptance. Hence it can be concluded that method was new, simple, selective, specific, precise for simultaneous estimation of Telmisartan and Metformin Hydrochloride in bulk powder.
Keywords: Telmisartan; Metformin HCl; Method validation; ICH guidelines; Stability; indicating; UV-Spectrophotometric